DETERMINANTS OF WRECKAGE COLLECTORS’ PROFIT IN CIREBON CITY - Zaenal Mutaqin; Istiqomah Istiqomah; Goro Binardjo (Faculty of Economics and Business, University of Pasundan, 2022)
Waste management has been a concern for the government because it is closely related to sustainable development. Wreckage collectors play a significant role in waste reduction and management. Therefore, the sustainability of the wreckage collector business, which is measured through profit performance, is interesting to investigate. This study aims to analyze the effect of education level, firm age, type of product, and capital on the profit of wreckage collectors in Cirebon city. The population consist of 40 wreckage collectors, all were selected as respondents. The data were analyzed with multiple linear regression using the OLS method. The results show that education, firm age, and capital have a positive and significant effect on the profit of wreckage collectors, while type of product has no significant effect. The results imply the need to improve education for wreckage collectors. In addition, financial institutions should facilitate low-interest loans to improve turnover and profit.